The psychological consequences of (perceived) ionizing radiation exposure: a review on its role in radiation-induced cognitive dysfunction. (1st September 2020) - Collett, George; Craenen, Kai; Young, William; Gilhooly, Mary; Anderson, Rhona M.
Abstract: Purpose: Exposure to ionizing radiation following environmental contamination (e.g., the Chernobyl and Fukushima nuclear accidents), radiotherapy and diagnostics, occupational roles and space travel has been identified as a possible risk-factor for cognitive dysfunction. The deleterious effects of high doses (≥1.0 Gy) on cognitive functioning are fairly well-understood, while the consequences of low (≤0.1 Gy) and moderate doses (0.1–1.0 Gy) have been receiving more research interest over the past decade. In addition to any impact of actual exposure on cognitive functioning, the persistent psychological stress arising from perceived exposure, particularly following nuclear accidents, may itself impact cognitive functioning. In this review we offer a novel interdisciplinary stance on the cognitive impact of radiation exposure, considering psychological and epidemiological observations of different exposure scenarios such as atomic bombings, nuclear accidents, occupational and medical exposures while accounting for differences in dose, rate of exposure and exposure type. The purpose is to address the question that perceived radiation exposure - even where the actual absorbed dose is 0.0 Gy above background dose - can result in psychological stress, which could in turn lead to cognitive dysfunction. In addition, we highlight the interplay between the mechanisms of perceived exposure (i.e., stress) and actual exposure (i.e., radiation-induced cellular damage), in the generation of radiation-induced cognitive dysfunction. In all, we offer a comprehensive and objective review addressing the potential for cognitive defects in the context of low- and moderate-dose IR exposures. Conclusions: Overall the evidence shows prenatal exposure to low and moderate doses to be detrimental to brain development and subsequent cognitive functioning, however the evidence for adolescent and adult low- and moderate-dose exposure remains uncertain. The persistent psychological stress following accidental exposure to low-doses in adulthood may pose a greater threat to our cognitive functioning. Indeed, the psychological implications for instructed cohorts (e.g., astronauts and radiotherapy patients) is less clear and warrants further investigation. Nonetheless, the psychosocial consequences of low- and moderate-dose exposure must be carefully considered when evaluating radiation effects on cognitive functioning, and to avoid unnecessary harm when planning public health response strategies.